A Drosophila orphan G protein-coupled receptor BOSS functions as a glucose-responding receptor: loss of boss causes abnormal energy metabolism. - Kohyama-Koganeya, A.; Kim, Y.J.; Miura, M.; Hirabayashi, Y. (Proceedings of the National Academy of Sciences of the United States of America, 2008)
Glucose, one of the most important nutrients for animals, acts as a regulatory signal that controls the secretion of hormones, such as insulin, by endocrine tissues. However, how organisms respond to extracellular glucose and how glucose controls nutrient homeostasis remain unknown. Here, we show that a putative Drosophila melanogaster G protein-coupled receptor, previously identified as Bride of sevenless (BOSS), responds to extracellular glucose and regulates sugar and lipid metabolism. We found that BOSS was expressed in the fat body, a nutrient-sensing tissue equivalent to mammalian liver and adipose tissues, and in photoreceptor cells. Boss null mutants had small bodies, exhibited abnormal sugar and lipid metabolism (elevated circulating sugar and lipid levels, impaired lipid mobilization to oenocytes), and were sensitive to nutrient deprivation stress. These phenotypes are reminiscent of flies defective in insulin signaling. Consistent with these findings are the observations that boss mutants had reduced PI3K activity and phospho-AKT levels, which indicates that BOSS is required for proper insulin signaling. Because human G protein-coupled receptor 5B and the seven-transmembrane domain of BOSS share the same sequence, our results also have important implications for glucose metabolism in humans. Thus, our study provides insight not only into the basic mechanisms of metabolic regulation but also into the pathobiological basis for diabetes and obesity.